Solvents for thermoporosimetry analysis of natural rubber networks. Issue 39 (28th June 2016) - Wirtz, Marcel; Rommel, Robert; López Valentín, Juan; Westermann, Stephan; Sportelli, Franco; Kayser, François
ABSTRACT: Thermoporosimetry is known as an analytical method to investigate network structures in swollen elastomers. Despite this interesting potential capability, only few investigations are published in literature which apply different solvents on differently crosslinked natural rubber samples. The choice of the solvent is critical as it strongly influences the separation of confined and bulk solvent transition signal, the confined solvent signal intensity and the peak width representing the pore size resolution. No critical comparison has been done in these investigations regarding the solvent choice related to peak separation, pore size resolution or signal intensity. Furthermore, no critical assessment is available relating thermoporosimetry results to solvent parameters to identify an optimal solvent regarding the mentioned criteria. This argument motivated the present investigation to identify the most appropriate solvents for the analysis of natural rubber compounds by thermoporosimetry. Different types of solvents (aliphatic, aromatic, non‐polar, and polar) were selected and benchmarked against each other. It was concluded that n‐heptane was identified as the best solvent for these investigations. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43998. Abstract :